1973
DOI: 10.1103/physrevc.8.114
|View full text |Cite
|
Sign up to set email alerts
|

H2(H2

Abstract: The d + d -d + p + n breakup reaction was studied over a range of bombarding energies Ed = 14-36 MeV. The proton and deuteron were detected at angle pairs chosen to either emphasize quasifree scattering (QFS) or the n-p final-state interaction (FSI). It was found that by using a smooth cutoff for the deuteron wave function, a modified plane-wave impulse-approximation(PODIA) theory could fit the magnitude and shape of the observed QFS peaks. To fit the QFS plus FSI data only triplet FSI was needed in contrast t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The PSDs used in the experiment were calibrated in energy using the elastic scattering peaks measured at different beam energies for the 6 Li + 197 Au, 6 Li + 12 C reactions and the 6 Li + 12 C → 14 N * + α reaction. Moreover, a three-peak alpha source ( 239 Pu − 241 Am − 244 Cm) was used to calibrate at low energies.…”
Section: Detector Calibration and Identification Of The 2 H( 6 LI α 3...mentioning
confidence: 99%
See 1 more Smart Citation
“…The PSDs used in the experiment were calibrated in energy using the elastic scattering peaks measured at different beam energies for the 6 Li + 197 Au, 6 Li + 12 C reactions and the 6 Li + 12 C → 14 N * + α reaction. Moreover, a three-peak alpha source ( 239 Pu − 241 Am − 244 Cm) was used to calibrate at low energies.…”
Section: Detector Calibration and Identification Of The 2 H( 6 LI α 3...mentioning
confidence: 99%
“…QF reactions of light nuclei have been studied extensively in the past at low and intermediate energies in order to investigate the nuclear structure [5][6][7][8][9]. In particular, due to the low binding energy of n-p in deuteron, n-d and d-d break-up reactions have been studied, in order to get information on the n-n and n-p interactions [10][11][12][13]. In the last few decades, the deuteron QF break-up has been exploited in the framework of the Trojan Horse method (THM) to study several proton-induced reactions at energies relevant for astrophysics, avoiding the Coulomb suppression and the electron screening effects [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Most experimental and theoretical works deal with the D(d, pn)D, D(d, nd)p, and D(d, pd)n reactions. In studying pd coincidences in the D(d, pd)n reaction at E D = 10-36 MeV, the authors of [1] pointed out that the main mechanisms for appear ance of deuterons in the reaction exit channel were quasifree processes in the pn interaction in the final triplet state. Contributions from various mechanisms to the deuteron breakup process at different angles can be evaluated by analyzing inclusive spectra of secondary particles [2][3][4][5], which can thus comple ment the information gained from exclusive mea surements.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the reaction mechanism of the sequential breakup process of the ( He, d*) reactions has been given recently by de Meijer [11]. Three-body breakup spectra from a kinematically complete measurement of the H(I2pi)n [12], H(p, pn )p [13],and H(d, dp )n [14] reactions have been analyzed to estimate the cross section for the production of d". Various authors [15 -17] have reported the evidence of d* production in the kinematically complete measurement of the H( paa)n reaction in which the shape of the energy-sharing distribution is peaked in the kinematic region where the n-p relative kinetic energy in the final state is zero (E"=O).…”
Section: Introductionmentioning
confidence: 99%